Sniper : the last stand [videorecording (DVD)] - Wathen, Sean; Collins, Chad Michael, 1979-; Robbins, Ryan, 1971-; Taylor, Sharon (Actress) (Sony Pictures, 2025)
To stop an arms dealer from unleashing a deadly superweapon, Ace sniper Brandon Beckett and Agent Zero are deployed to Costa Verde to lead a group of elite soldiers against an unrelenting militia. Taking an untested sniper under his wing, Beckett faces his newest challenge: giving orders instead of receiving them. With both time and ammo running low in a race to save humanity, the team must overcome all odds just to survive.